Evaluation of Fludarabine, and granulocyte colony stimulating factor in treatment of efractory/Relapsed Acute Leukemias in adult Iraqi patients - Alwan, Alaa Fadhil; Alaqabi, Adil siwan; Al-zubaidi, Azher (AL-Kindy College Medical Journal, 2012)
Background: Refractory/relapsed acute leukemia has always been a challenging problem for hematologist. Over the past decade emphasis has been made in the development of regimens containing fludarabine, combined with cytosine arabinoside for the treatment of refractory/relapsed acute leukemias. The aim of this study is to evaluate the efficacy and toxicity of the combination of fludarabine, high dose cytarabine, and granulocyte colony stimulating factor in refractory relapsed cases of acute leukaemia, Methods: a prospective study is being conducted at the national center of hematology and hematology unit /Baghdad teaching hospital from July 2008 to July 2010.Twenty Patients with refractory/relapsed acute leukemia were treated with fludarabine 30mg/m2 and cytosine arabinoside (AraC) 2 g/m2 for 5 days, and granulocyte colony stimulating factor G-CSF 300 microgram/day from day 0 till neutrophil recovery (ANC >1.0 x 109/l).Response was evaluated by bone marrow examination on day 30-post chemotherapy. Results: Patients included were refractory acute lymphoblastic leukemia (ALL) (n=5), relapsed ALL (n=4), refractory acute myeloid leukemia (AML) (n=8), relapsed AML (n=3). Complete remission (CR) was achieved in 9(45%) patients, 3 (15%) patients got partial remission. Three (15%) patients died of post chemotherapy complications and 5(25%) patient failed to achieve remission. Major complications encountered were: anemia, fever, bleeding, mucositis and bacterial infections. Conclusion: FLAG protocol is well tolerated and effective regimen in relapsed / refractory acute leukemias. The toxicity is acceptable, enabling most patients to receive further treatment, including transplantation procedures